2006
DOI: 10.1303/aez.2006.295
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Cry1Ab toxin, a Bacillus thuringiensis insecticidal toxin, to proteins of the bovine intestinal epithelial cell: An in vitro study

Abstract: Cry toxins produced by Bacillus thuringiensis are insecticidal toxins and have been recently introduced to genetically modified (GM) organisms. The toxins are considered harmless to humans and farm animals; however, it remains unclear whether the toxins affect the mammalian intestinal epithelium, the primary portal and absorption site after ingestion. Therefore, we performed immunohistochemical and ligand blot analyses using brush border membrane vesicles to investigate the interaction of Cry1Ab toxin, a popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Proteins in the PAGE gel were transferred onto PVDF membranes (Hybond-P; GE Healthcare) by Transblot SD (Bio-Rad). After blocking with skim milk, the membrane was incubated with rabbit antiserum against Cry1A toxin (40), then with peroxidase-labeled anti-rabbit antibody (GE Healthcare), and visualized using a HistMark TrueBlue Peroxidase System (KPL).…”
Section: Methodsmentioning
confidence: 99%
“…Proteins in the PAGE gel were transferred onto PVDF membranes (Hybond-P; GE Healthcare) by Transblot SD (Bio-Rad). After blocking with skim milk, the membrane was incubated with rabbit antiserum against Cry1A toxin (40), then with peroxidase-labeled anti-rabbit antibody (GE Healthcare), and visualized using a HistMark TrueBlue Peroxidase System (KPL).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Cry toxins do bind to mammalian proteins in vitro (Shimada et al, 2006b;Vazquez-Padron et al, 2000), but this interaction is mostly non-specific (Hofmann et al, 1988) and thus is not conducive to formation of toxin pores (Shimada et al, 2006a). More difficult to explain are reports of high affinity toxin binding, which suggests toxin insertion in the membrane (Liang et al, 1995), associated with low susceptibility, as in the case of Cry1Ac and Spodoptera frugiperda (Garczynski et al, 1991) or Lymantria dispar (Wolfersberger, 1990).…”
Section: Specificity Level Vii: Post-binding Eventsmentioning
confidence: 99%
“…An in vitro study on bovine intestinal cells [73] found that the Cry1Ab protein binds to the apical surface of enterocytes. Specifically, the protein was bound to actin, a major protein of the cytoskeleton.…”
Section: The Cry Proteins As a Source Of Rodent Toxicitymentioning
confidence: 99%